Systematic Literatur Review: Pengaruh Servant Leadership Terhadap Kinerja Karyawan - Heni Yuniarti; Rizki Agustina; Suprayogi Pamungkas; Dani Rizana (Journal of Literature Review, 2025)
This study aims to review and synthesize previous research findings on the influence of servant leadership on employee performance using the Systematic Literature Review (SLR) approach. This approach was employed to trace, analyze, and synthesize various prior studies relevant to the topic of servant leadership. Data collection was conducted through two main databases, namely Google Scholar and Emerald Insight, covering publications from 2019 to 2025. The selected articles were screened based on inclusion and exclusion criteria, assessed for topic relevance, and analyzed using a descriptive-qualitative approach to identify research patterns and trends. The synthesis results show that servant leadership has a positive and significant impact on employee performance across various sectors, including education, public service, and private organizations. This leadership style not only enhances job satisfaction, loyalty, and organizational commitment but also builds a collaborative and empowerment-oriented organizational culture. Core values such as empathy, ethics, and social responsibility have been proven to increase motivation, productivity, and employee well-being. Therefore, servant leadership can be regarded as an effective leadership approach that balances organizational goal achievement with human resource development.